Respuesta :

Answer:

[tex]x = 1\frac{5}{12} [/tex]

Step-by-step explanation:

[tex] \frac{5x}{3} - \frac{x - 2}{4} = 2 \frac{1}{4} - (x - \frac{2x - 1}{3} ) \\ \frac{5x}{3} - \frac{x - 2}{4} = \frac{9}{4} - x + \frac{2x - 1}{3} \\ \frac{20x}{12} - \frac{3x - 6}{12} = \frac{9}{4} - x + \frac{2x - 1}{3} \\ \frac{17x + 6}{12} = \frac{9 - x}{4} + \frac{2x - 1}{3} \\ \frac{17x + 6}{12} = \frac{27 - 3x}{12} + \frac{8x - 4}{12} \\ \frac{17x + 6}{12} = \frac{23 + 5x}{12} \\ 12(17x+ 6) = 12(23 + 5x) \\ 17x + 6 = 23 + 5x \\ 17x - 5x = 23 - 6 \\ 12x = 17 \\ x = \frac{17}{12} \\ x = 1 \frac{5}{12} \\ [/tex]